A Literature Review of Innovation Capabilities and Business Performance of Third-Party Logistics (3PL) Service Providers in Malaysia - Zulkiffli, Siti Nur ‘Atikah; Sebadak, Maisarah; Padlee, Siti Falindah; Mohd Yusoff, Juhaizi (International Journal of Supply Chain Management, 2019)
According to the Malaysian Government Transformation Programme, transportation is one of the national priority areas and plays a significant role in the country’s well-being and has contributed much to the development and improvement of the economic, social, political and cultural conditions of the nation. The role and contribution of transportation is very important in strategic business and it is also one of the key focal points in the Eleventh Malaysia Plan for 2016 to 2020. Moving forward, while the prospects for Malaysia’s logistics industry are positive, there is still much room for improvement in terms of business performance. Most companies selling or producing goods require facilitating agencies such as third-party logistics (3PL) providers to assist them in transporting their products and services from one destination to another until they reach the end customer. Therefore, this study focuses on a review of the literature on innovation capability and business performance among 3PL service providers in Malaysia. This study focuses on four attributes of innovation capability: (i) service innovation, (ii) process innovation, (iii) marketing innovation and (iv) management innovation. It contributes to the body of knowledge in this field by identifying the significant factors that influence innovativeness that will lead to a higher level of business performance among 3PL providers in Malaysia. Its findings also useful to 3PL practitioners and policy-makers, particularly in Malaysia and the Asian region.